Improving the layer morphology of solution-processed perylene diimide organic solar cells with the use of a polymeric interlayer - Singh, Ranbir; Mróz, Marta M.; Fonzo, Fabio Di; Cabanillas-González, Juan R.; Marchi, Enrico; Bergamini, Giacomo; Müllen, Klaus; Jacob, Josemon; Keivanidis, Panagiotis E. (My University, 2013)
Herein we demonstrate a method to improve the power conversion efficiency (PCE) parameter of organic photovoltaic (OPV) devices based on the electron acceptor N,N’-bis(1- ethylpropyl)-perylene-3,4,9,10-tetracarboxylic diimide (PDI) blended with the electron donor poly(indenofluorene)-aryloctyl (PIF-Aryl). The device parameters of the short-circuit current, open-circuit voltage and fill factor are found increased after the insertion of a thin poly [9, 9-dioctylfluorene-co-N- [4-(3-methylpropyl)]-diphenylamine] (TFB) photoactive interlayer between the hole-collecting electrode and the photoactive layer of the device. Unlike to most of the cases where interlayers serve as charge extractors, in our system the polymeric interlayer serves as a morphology modifying agent that drives the PDI component to segregate better at the interface with the device cathode; that is at the carrier-collecting electrode interface, which is not in physical contact with the interlayer. The processes of energy/charge transfer of the TFB excitons to/with the PIF-Aryl:PDI top-layer are also addressed. Charge transfer reactions dominate at the TFB/PIF-Aryl:PDI interface but no significant contribution in the photocurrent generation is seen in the photoaction spectra of the bilayer device.
Keywords: power conversion efficiency (PCE); organic photovoltaic (OPV)